Analisis semantik leksikal dalam novel Sangkar karya Samsiah Mohd. Nor = (Lexical Semantics Analysis in Sangkar Novel by Samsiah Mohd. Nor) - Siti Farida, Salleh; Yazid, Yahya; Mary Fatimah, Subet; Muhammad Zaid, Daud (Penerbit Universiti Sultan Zainal Abidin (UniSZA), 2020)
Novel is one of the mediums of non-verbal communication that the author wishes to convey to the reader. Through the reading of this novel, the reader can experience a wide range of emotions. Whether it's sad, happy, excited and so on. Therefore, this study will explore the meaning behind the novel entitled "Sangkar" by Samsiah Mohd. Nor. The novel was published in 2010 through the publication of Alaf 21 Sdn. Bhd. There are 248 pages and 26 chapters for this novel. This study is a qualitative study consisting of annotated text analysis as well as a simple quantitative approach to finding lexical frequency and complexity in this Sangkar novel. To analyze this novel the researcher will apply a lexical semantic approach. Through this lexical semantic approach it is possible to classify lexical types into synonyms, antonyms, hyponyms, polysemic, homonyms, homophones, homographs, metonyms and meronyms. Based on the findings of this study, the frequency and percentage of total lexical semantics recorded a frequency value of 1019 (100%) lexical only. However, through the novel there was only partial lexical semantics comprising; antonyms–442 (43.37%), synonyms–218 (21.39%), meronyms–185 (18.15%) and hyponyms–174 (17.07%). It can be concluded that through this lexical semantic approach it is possible to classify different lexical groups into the same group of meanings.